Stereoselective Michael Additions of Arylacetic Acid Derivatives by Asymmetric Organocatalysis - Kim, Byungjun; Kim, Yongjae; Lee, Sarah Yunmi (Synlett, 2022)
Because of the versatility of chiral 1,5-dicarbonyl structural motifs, the development of stereoselective Michael additions of arylacetic acid derivatives to electron-deficient alkenes is an important challenge. Over recent decades, an array of enantio- and diastereoselective methods of this type have been developed through the use of chiral organocatalysts. In this article, three distinct strategies in this research area are highlighted. Catalytic generation of either a chiral iminium electrophile (iminium catalysis) or a chiral enolate nucleophile (Lewis base catalysis) has allowed the efficient construction of stereogenic C–C bonds. We also introduce a synergistic catalytic approach involving the merger of these two catalytic cycles that provides selective access to all four stereoisomers of products with vicinal stereocenters.1 Introduction2 Iminium Catalysis3 Lewis Base Catalysis4 Synergistic Organocatalysis5 Summary
Keywords: asymmetric catalysis; organocatalysis; Michael addition; iminium catalysis; isothiourea catalysis; synergistic catalysis